The celebration of independence in Nicaragua (1866-1928) - Urbina Gaitán, Chester (2019)
The political contents that were transmitted during the acts of celebrating independence in Nicaragua between 1866 and 1895, can be divided into two periods, the first corresponds to the years from 1866 to 1875, where independence had brought equality between Nicaraguans, but these must be moralized, practice patriotism and work in order to cement political stability. Likewise, the arrival of the Central American union was long for. Between 1877 and 1895 the commemorative speeches of September 15 added political concepts that highlighted the "liberating" role of education. They promoted national unity and the ethnic regeneration of Nicaraguans, as the role of national hero José Dolores Estrada and the National Campaign is rescued. Economic progress and political stability brought by conservative governments are also exalted. These perorations served to manifest a class vision and maintain the prevailing form of domination. On the other hand, the texts published by the Nicaraguan press on the celebrations of September 15 during the period 1903-1928, expose the various political-cultural influences that existed at that time to address the issue of national identity and analyze the main problems which Nicaragua was going through, mainly that of the American occupation. These positions went from nationalism, anti-imperialism and unionism